MENINGKATKAN PERAN BADAN USAHA MILIK DESA DALAM MEMASARKAN PRODUK UNGGULAN LOKAL - Julianto Hutasuhut; Abd. Rasyid Syamsuri; Adrial Falahi; Ardhansyah Putra Harahap; Arief Hadian; Dwi Saraswati; Siti Lam'ah Nasution (Jurnal Abdimas Bina Bangsa, 2023)
Village-Owned Enterprises (BUMDes) have emerged as a novel alternative approach to enhancing the economy and welfare of rural communities by tapping into the potential of villages. However, the reality is that only a few BUMDes are able to positively contribute to economic development and the betterment of community welfare, including those in Pematang Johar village. To address this, a community service initiative was conducted in Pematang Johar village in the Medan Labuhan District of Deli Serdang Regency. The main objective of the program was to provide education and socialization on the "Marketing Mix" marketing strategy and the consignment sales system to the management of BUMDes Johar Mandiri, the manager of Sawah Tourism business, and micro and small businesses in Pematang Johar village. The aim was to enable BUMDes and the community to build more extensive business collaborations in local economic development and community welfare. The program in Pematang Johar village went according to plan, with partners displaying a cooperative and enthusiastic attitude throughout the activity. Furthermore, partners actively engaged in discussions and sought clarification, demonstrating increased motivation to follow up on the community service program. The activity had a direct impact on the partners, enhancing their comprehension of the "Marketing Mix" concept and the consignment sales system, and inspiring them to pursue business collaborations by implementing the program offered to develop Sawah Tourism in Pematang Johar. Ultimately, the partners hope for more intense collaboration as a follow-up to this community service program to further enhance community welfare in Pematang Johar village in the Medan Labuhan District of Deli Serdang Regency.